Polyester resin, polyester resin composition and molded product thereof
By introducing end capping groups of salts into the polyester resin, the crystallization speed and laser transmittance are improved, and the problem of insufficient laser transmittance during laser welding in the prior art is solved, and a more efficient and stable laser welding effect is achieved.
Patent Information
- Application Number
- CN202311069599.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-23
- Publication Date
- 2025-02-25
AI Technical Summary
The existing polyester resins lack laser transmittance during laser welding, resulting in insufficient heat absorption on the welding surface, inability to complete welding bonding, and increasing the laser intensity may lead to overheating and ablation of the material.
By introducing a specific catalyst at the end of the polyester molecular chain to introduce end capping groups of salts, the crystallization speed of the polyester resin is increased, and the grain size is reduced, thereby improving the laser transmittance.
The high laser transmittance of polyester resin is achieved, the problem of insufficient heat absorption on the welding surface is solved, the material is overheated and ablated, and the efficiency and quality of laser welding are improved.
Smart Images

Figure BDA0004411105340000251 
Figure BDA0004411105340000261 
Figure BDA0004411105340000271
Abstract
Description
Technical Field
[0001] The invention relates to a polyester resin with high laser transmittance, a polyester resin composition and a molded product thereof. Background Art
[0002] Polybutylene terephthalate (PBT) resin is widely used in mechanical parts, electrical communication parts, automotive parts and other fields due to its excellent properties such as heat resistance, chemical resistance, electrical properties, mechanical properties, and molding processability. In particular, its application in various automotive electrical installation parts has attracted widespread attention in recent years. However, these parts sometimes need to ensure their airtightness, and traditional joining methods such as screw fastening, adhesive bonding, hot plate welding, and ultrasonic welding have problems such as long process time and insufficient design freedom. Laser welding, as an external heating welding technology, is an engineering method that melts and fuses by irradiating a laser beam on a laminated resin molded body so that it passes through the irradiated surface and is absorbed by the other side. This method can achieve the requirements of three-dimensional connection, non-contact processing, and no welding overflow, so it has the characteristics of fast process, large design freedom, and high bonding strength, and has therefore attracted widespread attention. At the same time, it can be seen from the above laser welding process that the laser transmittance of the welding material is an important parameter. When laser welding is used to join PBT resin, if the laser transmittance of the resin is too low, it is easy to cause insufficient heat absorption at the welding surface, and ultimately the welding bonding cannot be completed; however, when the laser intensity is increased to compensate for the insufficient transmittance and increase the heat absorption of the welding surface, it is easy to cause the material to overheat and ablate and carbonize. Therefore, how to effectively improve the laser transmittance of the welding material has always been a problem of continuous concern in this field.
[0003] The spherulite microstructure of PBT scatters the incident laser to a greater extent than pure amorphous thermoplastic materials, resulting in reduced projection energy. In addition, slow scattering will cause the laser beam to become wider, resulting in impaired welding accuracy. There are many blending processing methods that increase the laser transmittance of PBT by adding crystallization nucleating agents, but there are defects such as reduced viscosity and uneven laser transmittance during processing. In order to improve these shortcomings, organic salt groups with crystallization nucleus function are introduced at the end of the molecular chain to increase the laser transmittance of PBT.
[0004] Patent document 1 (Japanese Patent Re-listing 2014 / 171402) discloses a water-dispersible and water-resistant polyester containing a sulfonate terminal modification, but the terminal sulfonate content is relatively large, resulting in an excessively low molecular weight. In addition, the polyester contains a trifunctional copolymer component, which makes it easy to undergo bridging crosslinking and cannot obtain a semi-crystalline thermoplastic polyester resin.
[0005] Patent document 2 (Chinese patent CN111718479A) discloses a cationically dyeable polyester containing sulfonate terminal modification, but the method cannot obtain a polymer with a high amount of sulfonate introduced.
[0006] Non-patent document 3 (Japanese document: Chemically Modified Engineering Plastics, "Forming Processing" Vol. 5, No. 9)) discloses a PBT polyester containing sulfonate end modification, whose crystallization temperature decreases from about 200°C to 190°C as the polymerization time progresses. This shows that the effect of the sulfonate end as a crystallization nucleus is limited, and the grain size cannot be made small enough, and the effect of improving laser transmittance is limited. Summary of the invention
[0007] In view of the above problems, an object of the present invention is to provide a polyester resin having high laser transmittance, a composition containing the polyester resin, and a molded article thereof.
[0008] After in-depth research, the inventors found that by using a specific catalyst, a certain amount of salt-type end-capping groups can be introduced into the ends of the polyester molecular chains, which can increase the crystallization rate of the polyester resin and reduce the grain size, thereby preparing a polyester resin with high laser transmittance, thereby achieving the purpose of the present invention.
[0009] That is, in order to achieve the above-mentioned object, the present invention has the following structure:
[0010] The polyester resin of the present invention is composed of a dicarboxylic acid monomer unit, a diol monomer unit and a terminal group unit; wherein the dicarboxylic acid monomer unit is mainly derived from an aromatic dicarboxylic acid and / or its derivatives capable of forming an ester; the diol monomer unit is mainly derived from an aliphatic diol having 4 to 10 carbon atoms, and the content of the terminal group unit is 0.3 mol% or more and 3 mol% or less relative to the total amount of monomer units derived from the dicarboxylic acid component in the polyester resin; the terminal group unit is characterized by a structure represented by Formula 1 or Formula 2; the polyester resin contains at least one of a transition metal or a post-transition metal, and the content thereof relative to the weight of the polyester resin is 80 ppm-1500 ppm;
[0011] -O-R1-XM Formula 1,
[0012] In Formula 1, R1 is an alkyl group having 2 to 20 carbon atoms, X is a sulfonic acid group, a carboxyl group, a phosphoric acid group, or a phosphonic acid group, and M is an alkali metal ion or an alkaline earth metal ion;
[0013] In Formula 2, R2 is an alkyl group having 1 to 20 carbon atoms, a phenyl group or an alkylbenzene, X is a sulfonic acid group, a carboxyl group, a phosphoric acid group or a phosphonic acid group, and M is an alkali metal ion or an alkaline earth metal ion.
[0014] The dicarboxylic acid component used in the present invention includes terephthalic acid and / or its derivatives capable of forming esters. The derivatives capable of forming esters of terephthalic acid include, for example, alcohol ester derivatives such as dimethyl terephthalate and diethyl terephthalate; other derivatives capable of forming esters such as terephthaloyl chloride. In addition, the dicarboxylic acid component of the present invention may also include one or more selected from the dicarboxylic acid components listed below and their derivatives capable of forming esters. Specifically, the following examples may be cited, but are not limited to the following examples: isophthalic acid, phthalic acid, 2,6-naphthalene dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, 2,3-naphthalene dicarboxylic acid, 1,4-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 1,8-naphthalene dicarboxylic acid, 4,4'-dicarboxy diphenylmethane, anthracene dicarboxylic acid, 4,4'-diphenyl dicarboxylic acid, diphenoxyethane dicarboxylic acid Aromatic dicarboxylic acids such as 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, cyclopentanedicarboxylic acid, or 4,4'-dicyclohexyldicarboxylic acid; aliphatic dicarboxylic acids such as oxalic acid, succinic acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedionic acid, and dimer acid; alkyl diesters and diacid chlorides corresponding to the above dicarboxylic acids are also cited as monomer raw materials.
[0015] In the present invention, the "dicarboxylic acid monomer units mainly derived from aromatic dicarboxylic acids and / or their ester-forming derivatives" means that the content of terephthalic acid and / or their ester-forming derivatives is 70 mol% or more, preferably 75 mol% or more, and more preferably 80 mol% or more relative to all dicarboxylic acid and / or their ester-forming derivatives monomer units as raw materials of the polyester resin. When the content of the monomer units derived from terephthalic acid and / or their ester-forming derivatives is greater than 80 mol%, the crystallinity of the polyester resin increases and the mechanical strength of the polyester resin is enhanced. It is more preferably 90 mol% or more, and even more preferably 95 mol% or more.
[0016] The diol component used in the present invention is mainly 1,4-butanediol. In addition, the diol component of the present invention may also include one or more diols selected from the following diols, and specific examples include but are not limited to the following examples: aliphatic diols such as ethylene glycol, 1,3-propylene glycol, 1,5-pentanediol, 1,6-hexanediol, or decanediol; aliphatic diols such as 1,1-cyclohexanedimethanol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, 1,4-dicyclohexanedimethanol, or tricyclodecanediol; Cyclic diols; aromatic diols such as benzyl alcohol, bis(p-hydroxy)biphenyl, bis(p-hydroxy)diphenylpropane, 2,2-bis[4-(2-hydroxyethoxy)phenyl]propane, bis[4-(2-hydroxyethoxy)phenyl]sulfone, 1,1-bis[4-(2-hydroxyethoxy)phenyl]cyclohexane, 4,4-dihydroxy-p-terphenyl, or 4,4-dihydroxy-p-quaterphenyl; the diols may also be used in the form of acetylated products or alkali metal salts.
[0017] The "diol monomer units are mainly derived from aliphatic diols having 4 to 10 carbon atoms" means that the content of 1,4-butanediol is 70 mol% or more, preferably 75 mol% or more, and more preferably 80 mol% or more relative to all diol monomer units used as raw materials for the polyester resin. By controlling within this range, the crystallinity of the polyester resin can be maintained, thereby maintaining high mechanical strength. Furthermore, the lower limit of the content is more preferably 85 mol% or more, more preferably 90 mol% or more, and most preferably 95 mol% or more.
[0018] The terminal unit component used in the present invention is shown in Formula 1 or Formula 2. In Formula 1, R1 is an alkyl group having 2 to 20 carbon atoms, X is a sulfonic acid group, a carboxyl group, a phosphoric acid group or a phosphonic acid group, and M is an alkali metal ion or an alkaline earth metal ion. In Formula 2, R2 is an alkyl group having 1 to 20 carbon atoms, a phenyl group or an alkylbenzene, X is a sulfonic acid group, a carboxyl group, a phosphoric acid group or a phosphonic acid group, and M is an alkali metal ion or an alkaline earth metal ion. The metal salt of the terminal group is preferably at least one of an aromatic sulfonate having a carboxylic acid group, an aliphatic sulfonate having a hydroxyl group or an aliphatic carboxylate. The metal salt is preferably at least one of a lithium salt, a potassium salt, a sodium salt or a calcium salt. Specific examples include, but are not limited to, sodium isethionate, potassium isethionate, lithium isethionate, calcium isethionate, sodium 3-hydroxy-1-propanesulfonate, sodium hydroxytetradecanesulfonate, sodium 3-carboxybenzenesulfonate, lithium 3-carboxybenzenesulfonate, sodium 3-carboxybenzenesulfonate, sodium N-(2-hydroxyethyl)piperazine-N'-(2-ethanesulfonic acid), sodium benzoate-3,5-disulfonate, sodium 2-hydroxybenzoate-5-sulfonate, etc. The invention also includes the following: acid salts or mixtures of these sulfonates; carboxylates such as sodium 5-hydroxyvalerate, sodium 2-hydroxybutyrate, sodium 3-hydroxybutyrate, sodium 4-hydroxybutyrate, sodium 5-hydroxyhexanoate, disodium 2-hydroxy-D-glutamate, potassium 2-hydroxypropane-1,2,3-propanetricarboxylate, or mixtures of these carboxylates; phosphates such as sodium hydroxyethylidene diphosphate, potassium 2-carboxyethylphenyl hypophosphite, lithium 2-phosphoglycolate, monosodium methylphosphonate, or mixtures of these phosphates. Among them, sodium isethionate, sodium hydroxytetradecanesulfonate, sodium 3-carboxybenzenesulfonate, sodium 5-hydroxyvalerate, and potassium 2-carboxyethylphenyl hypophosphite are more preferred, and sodium isethionate, sodium hydroxytetradecanesulfonate, sodium 3-carboxybenzenesulfonate, and sodium 5-hydroxyvalerate are finally preferred.
[0019] The content of the terminal unit represented by the structural formula 1 or 2 is 0.3 mol% or more and 3 mol% or less. From the perspective of the crystal nucleus effect, the content of the terminal unit represented by the structural formula 1 or 2 is preferably 0.5 mol% or more. On the other hand, from the perspective of maintaining a high molecular weight of the polyester resin, the content is preferably 2.8 mol% or less, and more preferably 2.5 mol% or less.
[0020] In the polyester resin of the present invention, the transition metal and / or post-transition metal element is preferably a metal element of Group IIB and / or Group IVA. Considering the reaction efficiency of the terminal group, the metal element is further preferably at least one of tin or zinc. Tin compounds as polymerization catalysts include dibutyltin oxide, methylphenyltin oxide, tetraethyltin, hexaethyltin dioxide, hexacyclohexyltin dioxide, didodecyltin oxide, monobutyltin oxide, triethyltin hydroxide, triphenyltin hydroxide, triisobutyltin acetate, dibutyltin diacetate, diphenyltin dilaurate, butyltin trichloride, dibutyltin dichloride, tributyltin chloride, dibutyltin sulfide, butyltin hydroxide, methylstannic acid, ethylstannic acid, butylstannic acid, tin compounds of alkylstannic acids such as tin compounds or mixtures of these tin compounds. Zinc compounds as polymerization catalysts include zinc acetate, zinc oxide, zinc peroxide, zinc sulfide, zinc carbonate, zinc hydroxide, zinc halide and other zinc compounds or mixtures of these zinc compounds. More preferred are monobutyltin oxide, zinc acetate and zinc oxide, and even more preferred is monobutyltin oxide.
[0021] From the perspective of improving the reaction efficiency to obtain a high molecular weight terminal modified polyester and a high terminal group introduction amount, the above-mentioned metal element content is preferably 80 ppm or more, more preferably 150 ppm or more, and even more preferably 200 ppm or more relative to the total amount of the polyester resin. On the other hand, from the perspective of maintaining the hydrolysis resistance and heat resistance of the polyester resin, the above-mentioned metal element content is preferably 1500 ppm or less, more preferably 1200 ppm or less, even more preferably 1100 ppm or less, and most preferably 1000 ppm or less.
[0022] The temperature difference (Tm-Tmc) between the melting point (Tm) and the crystallization temperature (Tmc) of the polyester resin in the present invention is preferably 25°C or less. The crystallization temperature and melting point of the polyester resin can be measured by the following method: in a nitrogen atmosphere, the obtained polyester resin is heated from 30°C to 250°C at a heating rate of 20°C / min to reach a fully molten state, and maintained at this temperature for 2 minutes, and then the polyester resin of the present invention is cooled from the molten state to 30°C at a cooling rate of 20°C / min using a differential scanning calorimeter, and maintained at this temperature for 2 minutes. The top temperature of the exothermic peak that appears during the cooling process is the crystallization temperature Tmc of the polyester resin. Then, the temperature is increased to 250°C at a heating rate of 20°C / min, and the top temperature of the endothermic peak that appears during the heating process is measured, which is the melting point Tm of the polyester resin. The temperature difference between the melting point and the crystallization temperature indicates the speed of its crystal nucleus formation and crystal growth. The smaller the temperature difference, the faster the crystal nucleus formation and crystal growth rate, so that smaller grains can be obtained and the laser transmittance will be greater. Therefore, from the perspective of nucleation and crystal growth rate, the temperature difference is more preferably below 22°C, and more preferably below 20°C. In addition, in the present invention, when multiple endothermic peak temperatures appear during the above-mentioned heating process, the highest endothermic peak temperature is the melting point.
[0023] The polyester resin of the present invention is heat-pressed into a 50 μm thick film at 25° C. above the melting point, and its transmittance measured by a spectrophotometer at a wavelength of 940 nm is preferably 40% or more. Considering that it can be used as a laser welding material, the transmittance is more preferably 45% or more.
[0024] In the present invention, the number average molecular weight (Mn) of the polyester resin is a value obtained by gel permeation chromatography using hexafluoroisopropanol as a solvent and then converted using polymethyl methacrylate (PMMA) as a standard sample. In order to further ensure the mechanical properties required for actual use, the number average molecular weight (Mn) is preferably in the range of 5000 or more and 20000 or less. Furthermore, the lower limit of the number average molecular weight is more preferably 5500 or more, and more preferably 6000 or more. On the other hand, in terms of melt molding processing, the upper limit of the number average molecular weight is more preferably 15000 or less, and more preferably 10000 or less.
[0025] The polyester resin of the present invention can be prepared by the following method: a raw material having a molar ratio of diol component to dicarboxylic acid component of 1.05-2.50 is subjected to an esterification reaction or an ester exchange reaction at a temperature range of 150-250°C under normal pressure or reduced pressure, and then a condensation reaction is carried out at a temperature of 240-270°C and a pressure of 500 Pa or less. Preferably, a compound having a structure of Formula 1 or 2 is added at the initial stage of the above-mentioned esterification or ester exchange reaction or the initial stage of the condensation reaction. In order to obtain a polyester resin with a high degree of polymerization, the reaction temperature of the condensation reaction at the temperature of 240-270°C and a pressure of 500 Pa or less is more preferably 245°C or more, and more preferably 248°C or more. On the other hand, in order to suppress thermal decomposition, the reaction temperature of the condensation reaction is more preferably 267°C or less, and more preferably 263°C or less.
[0026] -O-R1-XM Formula 1,
[0027] In Formula 1, R1 is an alkyl group having 2 to 20 carbon atoms, X is a sulfonic acid group, a carboxyl group, a phosphoric acid group or a phosphonic acid group, and M is an alkali metal ion or an alkaline earth metal ion.
[0028] In Formula 2, R2 is an alkyl group having 1 to 20 carbon atoms, a phenyl group or an alkylbenzene, X is a sulfonic acid group, a carboxyl group, a phosphoric acid group or a phosphonic acid group, and M is an alkali metal ion or an alkaline earth metal ion.
[0029] The compounds represented by Formula 1 and Formula 2 include, but are not limited to, the following examples: sodium isethionate, potassium isethionate, lithium isethionate, calcium isethionate, sodium 3-hydroxy-1-propanesulfonate, sodium hydroxytetradecanesulfonate, sodium 3-carboxybenzenesulfonate, lithium 3-carboxybenzenesulfonate, sodium 3-carboxybenzenesulfonate, sodium N-(2-hydroxyethyl)piperazine-N'-(2-ethanesulfonic acid), sodium 3,5-disulfonate, sodium 2-hydroxybenzoic acid-5 Sulfonates such as sodium 2-hydroxybutyrate or mixtures of these sulfonates; carboxylates such as sodium 5-hydroxyvalerate, sodium 2-hydroxybutyrate, sodium 3-hydroxybutyrate, sodium 4-hydroxybutyrate, sodium 5-hydroxyhexanoate, disodium 2-hydroxy-D-glutamate, potassium 2-hydroxypropane-1,2,3-propanetricarboxylate or mixtures of these carboxylates; phosphates such as sodium hydroxyethylidene diphosphate, potassium 2-carboxyethylphenyl hypophosphite, lithium 2-phosphoglycolate, monosodium methylphosphonate or mixtures of these phosphates. Among them, sodium hydroxyethyl sulfonate, sodium hydroxytetradecane sulfonate, sodium 3-carboxybenzenesulfonate, sodium 5-hydroxyvalerate, potassium 2-carboxyethylphenyl hypophosphite are more preferred, and sodium hydroxyethyl sulfonate, sodium hydroxytetradecane sulfonate, sodium 3-carboxybenzenesulfonate, sodium 5-hydroxyvalerate, and potassium 2-carboxyethylphenyl hypophosphite are finally preferred.
[0030] In the present manufacturing method, the tin and / or zinc compounds added in the esterification or transesterification reaction or condensation reaction stage can specifically list the following examples but are not limited to the following examples: dibutyltin oxide, methylphenyltin oxide, tetraethyltin, hexaethyltin dioxide, hexacyclohexyltin dioxide, didodecyltin oxide, monobutyltin oxide, triethyltin hydroxide, triphenyltin hydroxide, triisobutyltin acetate, dibutyltin diacetate, diphenyltin dilaurate, butyltin trichloride, dibutyltin dichloride, tributyltin chloride, dibutyltin sulfide, butyl hydroxytin oxide, methyl stannic acid, ethyl stannic acid, butyl stannic acid, and other tin compounds of alkyl stannic acids or mixtures of these tin compounds and other organic tin compounds. The zinc compound as a polymerization catalyst can specifically be listed as zinc compounds such as zinc acetate, zinc oxide, zinc peroxide, zinc sulfide, zinc carbonate, zinc hydroxide, zinc halide, or mixtures of these zinc compounds. More preferably, monobutyltin oxide, zinc acetate and zinc oxide are preferred, and more preferably, monobutyltin oxide is preferred.
[0031] In addition, the present invention also relates to a polyester resin composition comprising the polyester resin. Furthermore, the polyester resin composition may further comprise a filler. The filler may include, but is not limited to, the following examples: fibrous inorganic or organic fillers such as glass fiber, carbon fiber, potassium titanate whisker, zinc oxide whisker, aluminum borate whisker, aluminum oxide fiber, silicon carbide fiber, ceramic fiber, asbestos fiber, gypsum fiber or metal fiber; and non-fibrous inorganic fillers such as wollastonite, zeolite, sericite, kaolin, mica, talc, clay, pyrophyllite, bentonite, montmorillonite, asbestos, silicate, aluminum oxide, silicon oxide, magnesium oxide, zirconium oxide, titanium oxide, iron oxide, calcium carbonate, magnesium carbonate, dolomite, calcium sulfate, barium sulfate, magnesium hydroxide, calcium hydroxide, aluminum hydroxide, glass microspheres, ceramic microspheres, boron nitride, silicon carbide or silicon dioxide. The above-mentioned filling material can be hollow. In addition, the above-mentioned filling material can also be treated with coupling agents such as isocyanate compounds, organic silane compounds, organic titanate compounds, organic borane compounds or epoxy compounds. The above-mentioned montmorillonite can also be an organic montmorillonite after the interlamellar ions are cation exchanged by organic ammonium salts. From the perspective of improving the mechanical properties of the polyester resin composition and reducing its molding shrinkage, the above-mentioned filling material is preferably a fibrous inorganic filling material, and more preferably glass fiber or carbon fiber. The cross-sectional shape of the fibrous filling material is not particularly limited, and can be circular or flat. In addition, the above-mentioned filling material can be added alone or in combination of two or more.
[0032] In the polyester resin composition, the mixing amount of the filler is preferably 0.1-150 parts by weight relative to 100 parts by weight of the polyester resin. The lower limit of the mixing amount of the filler is more preferably 10 parts by weight or more, and more preferably 30 parts by weight or more. On the other hand, the upper limit of the mixing amount of the filler is preferably 100 parts by weight or less, and more preferably 80 parts by weight or less.
[0033] The polyester resin composition of the present invention may also contain additives such as stabilizers, nucleating agents, antioxidants, mold release agents, flame retardants and masterbatches.
[0034] Examples of the stabilizer include phosphoric acid, trimethyl phosphate, triethyl phosphate, triethyl phosphonoacetate, 3,9-bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, and tetrakis(2,4-di-tert-butyl-5-methylphenyl)[1,1-biphenyl]-4,4'-diylbisphosphonate.
[0035] The nucleating agent may be one or more of an inorganic crystal nucleating agent or an organic crystal nucleating agent. The inorganic crystal nucleating agent may be, for example, silicon dioxide, aluminum oxide, zirconium oxide, titanium oxide, wollastonite, kaolin, talc, mica, or silicon carbide.
[0036] In addition, the organic crystal nucleating agent may be, for example, aliphatic carboxylic acid amides, carboxylic acid metal salts, or sorbitol derivatives. Among the aliphatic carboxylic acid amides, there can be listed aliphatic monocarboxylic acid amides such as lauric acid amide, palmitic acid amide, oleic acid amide, stearic acid amide, erucic acid amide, behenic acid amide, ricinoleic acid amide, or hydroxystearic acid amide; N-substituted aliphatic monocarboxylic acid amides such as N-oleyl palmitamide, N-oleyl oleic acid amide, N-oleyl stearic acid amide, N-stearyl oleic acid amide, N-stearyl stearic acid amide, N-stearyl erucic acid amide, N-hydroxymethyl stearic acid amide, or N-hydroxymethyl behenic acid amide; methylene bis stearic acid amide, ethylene bis lauric acid amide, ethylene bis capric acid amide, ethylene bis oleic acid amide, ethylene bis stearic acid amide, ethylene bis erucic acid amide, ethylene bis behenic acid amide, ethylene bis isostearic acid amide, ethylene bis hydroxystearic acid amide, butylene bis stearic acid amide, hexamethylene bis oleic acid amide, hexamethylene bis stearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene bishydroxystearic acid amide, isophthalic acid bisstearic acid amide, or isophthalic acid bis-12-hydroxystearic acid amide; N, N'-dioleyl sebacic acid amide, N, N'-dioleyl adipic acid amide, N, N-distearyl adipic acid amide, N, N'-distearyl sebacic acid amide, N, N'-distearyl isophthalic acid amide N-substituted aliphatic carboxylic acid diamides such as amine, or N,N'-distearyl terephthalic acid amide; N-butyl-N'-stearyl urea, N-propyl-N'-stearyl urea, N-stearyl-N'-stearyl urea, N-phenyl-N'-stearyl urea, xylylene distearyl urea, tolyl distearyl urea, hexamethylene distearyl urea, diphenylmethane distearyl urea, or diphenylmethane dilauryl urea.
[0037] Examples of the carboxylic acid metal salt include sodium benzoate, potassium benzoate, lithium benzoate, calcium benzoate, magnesium benzoate, barium benzoate, lithium terephthalate, sodium terephthalate, potassium terephthalate, calcium oxalate, sodium laurate, potassium laurate, sodium myristate, potassium myristate, calcium myristate, sodium dioctadecanoate, calcium dioctadecanoate, sodium stearate, potassium stearate, lithium stearate, calcium stearate, magnesium stearate, barium stearate, sodium montanate, calcium montanate, sodium benzoate, sodium salicylate, potassium salicylate, zinc salicylate, aluminum dibenzoate, potassium dibenzoate, lithium dibenzoate, sodium naphthalene dicarboxylate, and sodium cyclohexanecarboxylate.
[0038] Examples of the sorbitol derivatives include bis(p-methylbenzal)sorbitol, bis(p-ethylbenzal)sorbitol, bis(p-chlorobenzal)sorbitol, bis(p-bromobenzal)sorbitol, or sorbitol derivatives obtained by chemically modifying the above sorbitol derivatives.
[0039] Considering the effect of promoting the crystallization of the polyester resin, the nucleating agent is preferably silica, wollastonite, kaolin, talc, mica or aliphatic carboxylic acid amide. In addition, in the polyester resin composition of the present invention, the content of the nucleating agent is preferably 0.05 to 5 parts by weight relative to 100 parts by weight of the polyester resin. Within this range, the effect of promoting crystallization can be maintained, and a polyester resin composition with excellent toughness can be obtained. Furthermore, the lower limit of the content of the nucleating agent is more preferably 0.1 parts by weight or more, and the upper limit is more preferably 3 parts by weight or less, and more preferably 2 parts by weight or less.
[0040] The antioxidant is preferably at least one of a phenolic antioxidant or a sulfur antioxidant. In order to obtain better heat resistance and thermal stability, it is preferred to use a phenolic antioxidant and a sulfur antioxidant in combination.
[0041] The phenolic antioxidants include 2,4-dimethyl-6-tert-butylphenol, 2,6-di-tert-butylphenol, 2,6-di-tert-butyl-p-cresol, 2,6-di-tert-butyl-4-ethylphenol, 4,4'-butylenebis(6-tert-butyl-3-methylphenol), 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), Phenol), octadecyl-3-(3',5'-di-tert-butyl-4'-hydroxybenzene) propionate, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxybenzene)] propionate], 1,1,3-tris(2-methyl-4-hydroxy-5-di-tert-butylphenyl)butane, tris(3,5-di-tert-butyl-4-hydroxybenzyl) isocyanurate, triethylene glycol-bis[3-(3-tert-butyl-4-hydroxy-5- 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], 2,4-bis(n-octylthio)-6-(4-hydroxy-3,5-di-tert-butylanilino)-1,3,5-triazine, 2,2-thiodiethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], N,N'-hexamethylenebis(3,5-di-tert-butyl- 4-hydroxyhydrocinnamic acid), diethyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, 2,4-bis[(octylthio)methyl]o-cresol, or isooctyl-3-(3,5-di-tert-butyl-4-hydroxybenzene)propionate, etc.
[0042] Examples of the sulfur antioxidant include dilauryl thiodipropionate, dimyristyl thiodipropionate, distearyl thiodipropionate, ditridecyl thiodipropionate, pentaerythritol (3-lauryl thiopropionate), and 2-mercaptobenzimidazole.
[0043] The antioxidants mentioned above may be used alone, or two or more antioxidants may be used in combination because a synergistic effect may be produced by combining two or more antioxidants.
[0044] In the polyester resin composition of the present invention, the content of the antioxidant is preferably 0.01-3 parts by weight relative to 100 parts by weight of the polyester resin. Within this range, the antioxidant effect can be maintained and the generation of gas during melt processing can be suppressed. Further, the lower limit of the content of the antioxidant is more preferably 0.05 parts by weight or more, and more preferably 0.1 parts by weight or more. In addition, the upper limit is more preferably 2 parts by weight or less, and more preferably 1 part by weight or less.
[0045] The release agent is not particularly limited, and any release agent used for conventional thermoplastic resins can be used. Specifically, fatty acids, fatty acid metal salts, hydroxy fatty acids, fatty acid esters, aliphatic partially saponified esters, paraffins, low molecular weight polyolefins, fatty acid amides, alkylene bis fatty acid amides, aliphatic ketones, fatty acid lower alcohol esters, fatty acid polyol esters, fatty acid polyglycol esters, or modified polysiloxanes can be cited.
[0046] The fatty acid is preferably a fatty acid having 6 to 40 carbon atoms, and specific examples thereof include oleic acid, lauric acid, stearic acid, hydroxystearic acid, behenic acid, arachidonic acid, linoleic acid, linolenic acid, ricinoleic acid, palmitic acid, stearic acid, montanic acid, or a mixture thereof.
[0047] The fatty acid metal salt is preferably an alkali metal salt or alkaline earth metal salt of a fatty acid having 6 to 40 carbon atoms, and specific examples thereof include calcium stearate, sodium montanate, and calcium montanate.
[0048] The hydroxy fatty acid may be exemplified by 1,2-hydroxy fatty acid.
[0049] Examples of the fatty acid esters include stearic acid esters, oleic acid esters, linoleic acid esters, linolenic acid esters, adipate esters, behenic acid esters, arachidonic acid esters, montanic acid esters, isostearic acid esters, and esters of polymeric acids.
[0050] Examples of the aliphatic partially saponified ester include montanic acid partially saponified ester.
[0051] The alkane is preferably an alkane having 18 or more carbon atoms, and examples thereof include liquid paraffin, natural paraffin, microcrystalline wax, and petrolatum.
[0052] The low molecular weight polyolefin is preferably a polyolefin having a weight average molecular weight of 5000 or less, and specific examples thereof include polyethylene wax, maleic acid-modified polyethylene wax, oxidized polyethylene wax, chlorinated polyethylene wax, and polypropylene wax.
[0053] The fatty acid amide is preferably a fatty acid amide having 6 or more carbon atoms, and specific examples thereof include oleic acid amide, erucic acid amide, and behenic acid amide.
[0054] The alkylenebisfatty acid amide is preferably an alkylenebisfatty acid amide having 6 or more carbon atoms, and specific examples thereof include methylenebisstearamide, ethylenebisstearamide, and N,N-bis(2-hydroxyethyl)stearamide.
[0055] Examples of the aliphatic ketone include higher aliphatic ketones.
[0056] The fatty acid lower alcohol ester is preferably a fatty acid lower alcohol ester having 6 or more carbon atoms, and specific examples thereof include ethyl stearate, butyl stearate, ethyl behenate, and rice wax.
[0057] Examples of the fatty acid polyol ester include glycerol monostearate, pentaerythritol monostearate, pentaerythritol tetrastearate, pentaerythritol adipic acid stearate, dipentaerythritol adipic acid stearate, and sorbitan monostearate.
[0058] The fatty acid polyglycol ester may be polyethylene glycol fatty acid ester or polypropylene glycol fatty acid ester.
[0059] Examples of the modified polysiloxane include methylstyryl-modified polysiloxane, polyether-modified polysiloxane, higher fatty acid alkoxy-modified polysiloxane, higher fatty acid-containing polysiloxane, higher fatty acid ester-modified polysiloxane, methacrylic acid-modified polysiloxane, and fluorine-modified polysiloxane.
[0060] The flame retardant may be exemplified by bromine-based flame retardants, including decabromodiphenyl ether, octabromodiphenyl ether, tetrabromodiphenyl ether, tetrabromophthalic anhydride, hexabromocyclododecane, bis(2,4,6-tribromophenoxy)ethane, ethylenebistetrabromophthalimide, hexabromobenzene, 1,1-sulfonyl[3,5-dibromo-4-(2,3-dibromopropoxy)]benzene, polydibromophenylene oxide, tetrabromobisphenol-S, tris(2,3-dibromopropyl)isocyanurate, tribromophenol, tribromophenyl allyl ether, tribromoneopentyl alcohol, brominated polystyrene, brominated polyethylene, tetrabromobisphenol-A, tetrabromobisphenol-A derivatives, brominated epoxy resins, The flame retardant may be a chlorine-based flame retardant such as tetrabromobisphenol-A-epoxide oligomer or polymer and brominated phenol novolac epoxide, tetrabromobisphenol-A-carbonate oligomer or polymer, tetrabromobisphenol-A-bis(2-hydroxydiethyl ether), tetrabromobisphenol-A-bis(2,3-dibromopropyl ether), tetrabromobisphenol-A-bis(allyl ether), tetrabromocyclooctane, ethylenebispentabromodiphenyl, tris(tribromoneopentyl)phosphate, poly(pentabromobenzyl polyacrylate), octabromotrimethylphenyl indane, dibromoneopentyl glycol, pentabromobenzyl polyacrylate, dibromocresyl glycidyl ether, or N,N'-ethylene-bis-tetrabromoterephthalimide, etc. In the present invention, the flame retardant may also be a chlorine-based flame retardant, including chlorinated paraffin, chlorinated polyethylene, perchlorocyclopentadecane, or tetrachlorophthalic anhydride, etc.
[0061] The polyester resin of the present invention or the composition containing the polyester resin of the present invention can be molded into a molded product of a desired shape by any molding method such as injection molding, extrusion molding, blow molding, vacuum molding, melt spinning, or film molding.
[0062] The molded article made of the polyester resin of the present invention or the composition containing the polyester resin of the present invention can be used as mechanical structural parts, electrical parts, electronic parts, and automobile parts due to its good mechanical properties and heat resistance. Since the molded article of the present invention has high laser transmittance, it can be used particularly as a laser welding part.
[0063] Mechanical structural parts, electrical parts, electronic parts and automotive parts can be specifically listed as: circuit breakers, electromagnetic switches, focusing boxes, flyback transformers, fixing parts of copiers and printers, general household electrical appliances, housing protection parts of OA machines, variable capacitors, various terminal boards, converters, printed circuit boards, housing protection parts, terminal blocks, coil skeletons, connectors, relays, disk drive brackets, transformers, switch parts, socket parts, motor parts, sockets, plugs, concentrators, various shells, resistors, metal terminals and wire combinations of electrical and electronic parts, computer-related parts, audio parts and other sound parts, lighting parts, telecommunications equipment related parts, telephone equipment related parts, air conditioning parts, VTR, television and other home appliance parts, copier parts, fax parts, optical instrument parts, automobile ignition device parts, automobile connectors, and various automotive electrical parts. DETAILED DESCRIPTION
[0064] The present invention is specifically described below by way of examples, but the present invention is not limited thereto.
[0065] Various properties of the polyester resins obtained in the examples and comparative examples were measured by the following methods.
[0066] (1) Determination of terminal modifier unit content
[0067] The polyester resin prepared in each embodiment or comparative example was dissolved in deuterated HFIP (hexafluoroisopropanol) at a concentration of 30 mg / ml, and 1H-NMR nuclear magnetic test was performed using JEOLEC X400P of JEOL under the condition of 256 scans. The peaks corresponding to hydrogen on various structures in the 1H-NMR spectrum and the peaks corresponding to hydrogen on the monomer units derived from terephthalic acid and / or its derivatives that can form esters of the main chain repeating units of the polyester as the main component were attributed, and the peak areas were integrated for each peak. The peak areas corresponding to hydrogen on the monomer units derived from terephthalic acid and / or its derivatives that can form esters of the polyester main chain were used as the basis, and the contents of various structural units in the polyester resin were calculated in combination with the number of hydrogen atoms contained in each structure.
[0068] (2) Metal Atom Content Test
[0069] 5 g of the polyester resin obtained in each embodiment or comparative example was weighed, melted on a hot plate, pressed into a plate using a hydraulic press (LITH-SYP-3T) manufactured by Xiamen LithMachine Limited, and then tested using an X-ray fluorescence spectrometer (X-Calibur) manufactured by Xenemetrix.
[0070] (3) Melting point (Tm) and crystallization temperature (Tmc)
[0071] Using a TA DSC-discover250 analytical instrument, accurately weigh about 5 mg of the polyester resin sample obtained in the embodiment or comparative example, and test it under the following conditions. In a nitrogen atmosphere, the obtained polyester resin is heated from 30°C to 250°C at a heating rate of 20°C / min to reach a fully molten state, and is kept at this temperature for 2 minutes. Then, using a differential scanning calorimeter, the polyester resin of the present invention is cooled from the molten state to 30°C at a cooling rate of 20°C / min, and is kept at this temperature for 2 minutes. During this cooling process, the top temperature of the exothermic peak where crystallization occurs is the crystallization temperature Tmc of the polyester resin. Then, the temperature is increased to 250°C at a heating rate of 20°C / min, and the top temperature of the endothermic peak that appears during this heating process is measured as the melting point Tm.
[0072] (4) Laser transmittance
[0073] The polyester resin sample obtained in the embodiment or comparative example is melted at 25°C above the melting point for 3 minutes using a hot press and then hot pressed into a film, cooled in air to form a film with a thickness of 50 μm, then spontaneously cooled in air, and then scanned on a spectrophotometer (Japan SCOP Corporation, V-670) at a speed of 200 nm / min in the wavelength range of 1100 to 400 nm, and the transmittance at a wavelength of 940 nm is measured.
[0074] (5) Number average molecular weight (Mn)
[0075] 2.5 mg of the polyester resin prepared in each example or comparative example was dissolved in 4 ml of hexafluoroisopropanol containing 0.0075 molar equivalent of sodium trifluoroacetate, filtered through a filter with a pore size of 0.45 μm, and then the number average molecular weight Mn was determined by GPC. The GPC measurement conditions are as follows:
[0076] Pump: e-Alliance GPC system (manufactured by Waters)
[0077] Detector: Differential detector Waters 2414 (manufactured by Waters)
[0078] Chromatographic column: Shodex HFIP-806M (2 pieces) + HFIP-LG
[0079] Solvent: Hexafluoroisopropanol (with 0.0075N sodium trifluoroacetate added)
[0080] Flow rate: 0.5ml / min
[0081] Sample injection volume: 0.1ml
[0082] Temperature: 40℃
[0083] Molecular weight calibration: polymethyl methacrylate.
[0084] The raw materials used in the embodiments and comparative examples are as follows:
[0085] Terephthalic acid (TPA): Mitsui Chemicals Co., Ltd.
[0086] 1,4-Butanediol (BDO): Mitsubishi Chemical Corporation
[0087] Sodium Isethionate (SHES): Shanghai Aladdin Biochemical Technology Co., Ltd.
[0088] Tetrabutyl titanate (TBT): TCI (Shanghai) Chemical Industry Development Co., Ltd.
[0089] Monobutyltin oxide (II) (MBO): TCI (Shanghai) Chemical Industry Development Co., Ltd.
[0090] Sodium 3-hydroxy-1-propanesulfonate (HO-C3-SO3Na): Shanghai Aladdin Biochemical Technology Co., Ltd.
[0091] Sodium Hydroxytetradecane Sulfonate (HO-C14-SO3Na): Shanghai Jinjinle Industrial Co., Ltd.
[0092] Sodium 5-hydroxyvalerate (HO-C4-COONa): Henan Weitixi Chemical Technology Co., Ltd.
[0093] Calcium 5-hydroxyvalerate (HO-C4-COOCa): Henan Weitixi Chemical Technology Co., Ltd.
[0094] Sodium 3-carboxybenzenesulfonate (HOOC-B-SO3Na): Shanghai Aladdin Biochemical Technology Co., Ltd.
[0095] M1000: Huntsman Jeffamine M-1000
[0096] Benzoic acid (HOOC-B): Shanghai Aladdin Biochemical Technology Co., Ltd.
[0097] ZnAc2: Shanghai Aladdin Biochemical Technology Co., Ltd.
[0098] ZnO: Shanghai Aladdin Biochemical Technology Co., Ltd.
[0099] Sb2O3: Shanghai Aladdin Biochemical Technology Co., Ltd.
[0100] 1,7-Heptanediol (HO-C7-OH): Shanghai Aladdin Biochemical Technology Co., Ltd.
[0101] 1,10-Decanediol (HO-C10-OH): Shanghai Aladdin Biochemical Technology Co., Ltd.
[0102] Isophthalic acid (IPA): Shanghai Aladdin Biochemical Technology Co., Ltd.
[0103] 1,12-Dodecanedioic acid (HOOC-C10-COOH): Shanghai Aladdin Biochemical Technology Co., Ltd.
[0104] Ethylene glycol (EG): Shanghai Aladdin Biochemical Technology Co., Ltd.
[0105] Pentaerythritol (PER): Shanghai Aladdin Biochemical Technology Co., Ltd.
[0106] 5-Sodium Sulfonisophthalate (5-SSIPA): Shanghai Aladdin Biochemical Technology Co., Ltd.
[0107] Example 1
[0108] 0.640 mol of terephthalic acid (TPA, 106.2 g), 1.15 mol of 1,4-butanediol (1,4-BDO, 103.6 g), tin compound catalyst MBO (added amount: 0.042 wt% relative to the mass of the final terminal modified polyester resin), and antioxidant IR1010 (added amount: 0.019 wt% relative to the mass of the final terminal modified polyester resin) were added to a 250 ml four-necked flask reactor equipped with a distillation tower, nitrogen was introduced and stirring began, and the temperature was quickly raised to 100° C., and then the ester exchange reaction was started under normal pressure. At the same time, the temperature was slowly raised, and the esterification reaction was carried out for a period of time under the condition that the final temperature reached 238° C., and then the reaction was terminated and the oligomer melt was poured out.
[0109] The obtained prepolymer, tin compound catalyst MBO (addition amount: 0.021wt% relative to the mass of the final terminal-modified polyester resin), pentaerythritol tetra[3-[3,5-di-tert-butyl-4-hydroxyphenyl]propionate (antioxidant IR1010, addition amount: 0.031wt% relative to the mass of the final terminal-modified polyester resin), and terminal modifier sodium isethionate (0.35mol% relative to the total mole of the dibasic acid unit) were added to a dedicated polycondensation reaction tube. The reaction tube was then placed in an oil bath at 255°C and polycondensation was carried out under a pressure of less than 300Pa. The polycondensation reaction was stopped after the torque of the stirrer reached the target value, and the terminal-modified polyester resin was discharged. The results are shown in Table 1.
[0110] Example 2
[0111] Example 1 was repeated except that the terminal modifier SHES was 0.45 mol %. The results are shown in Table 1.
[0112] Example 3
[0113] Example 1 was repeated except that the terminal modifier SHES was 0.7 mol %. The results are shown in Table 1.
[0114] Example 4
[0115] Example 1 was repeated except that the terminal modifier SHES was 1.0 mol %. The results are shown in Table 1.
[0116] Example 5
[0117] Example 1 was repeated, except that the terminal modifier SHES was 1.5 mol %, and in the polycondensation reaction, the tin compound catalyst MBO was 0.042 wt %. The results are shown in Table 1.
[0118] Example 6
[0119] Example 1 was repeated, except that the terminal modifier SHES was 2.0 mol %, and in the polycondensation reaction, the tin compound catalyst MBO was 0.042 wt %. The results are shown in Table 1.
[0120] Example 7
[0121] Example 1 was repeated, except that the terminal modifier SHES was 2.8 mol %, and in the polycondensation reaction, the tin compound catalyst MBO was 0.042 wt %. The results are shown in Table 1.
[0122] Example 8
[0123] Example 1 was repeated, except that the terminal modifier SHES was 3.6 mol %, and in the polycondensation reaction, the tin compound catalyst MBO was 0.042 wt %. The results are shown in Table 1.
[0124] Comparative Example 1
[0125] Example 1 was repeated except that the terminal modifier SHES was 0.2 mol %. The results are shown in Table 1.
[0126] Comparative Example 2
[0127] Example 1 was repeated, except that the terminal modifier SHES was 4.5 mol %, and in the polycondensation reaction, the tin compound catalyst MBO was 0.042 wt %. The results are shown in Table 1.
[0128] Comparative Example 3
[0129] Example 1 was repeated except that the terminal modifier SHES was not added. The results are shown in Table 1.
[0130] Example 9
[0131] Example 1 was repeated, except that the terminal modifier was sodium 3-hydroxy-1-propanesulfonate (HO-C3-SO3Na) and the addition amount was 1.0 mol%. The results are shown in Table 2.
[0132] Example 10
[0133] Example 1 was repeated, except that the terminal modifier was sodium hydroxytetradecane sulfonate (HO-C14-SO3Na) and the addition amount thereof was 1.0 mol%. The results are shown in Table 2.
[0134] Embodiment 11
[0135] Example 1 was repeated, except that the terminal modifier was sodium 5-hydroxyvalerate (HO-C4-COONa) and the addition amount was 1.0 mol%. The results are shown in Table 2.
[0136] Example 12
[0137] Example 1 was repeated, except that the terminal modifier was calcium 5-hydroxyvalerate (HO-C4-COOCa) and the addition amount thereof was 1.0 mol %. The results are shown in Table 2.
[0138] Embodiment 13
[0139] Example 1 was repeated, except that the terminal modifier was sodium 3-carboxybenzenesulfonate (HOOC-B-SO3Na), and the addition amount thereof was 1.0 mol%. The results are shown in Table 2.
[0140] Comparative Example 4
[0141] Example 1 was repeated except that the terminal modifier was M1000, and the addition amount thereof was 1.0 mol %. The results are shown in Table 2.
[0142] Comparative Example 5
[0143] Example 1 was repeated, except that the terminal modifier was benzoic acid (HOOC-B) and the addition amount thereof was 1.0 mol %. The results are shown in Table 2.
[0144] Embodiment 14
[0145] Example 4 was repeated, except that the amounts of catalyst MBO added twice were 0.021 wt % and 0 wt %, respectively. The results are shown in Table 3.
[0146] Embodiment 15
[0147] Example 4 was repeated, except that the amounts of catalyst MBO added twice were 0.042 wt% and 0 wt% respectively. The results are shown in Table 3.
[0148] Example 16
[0149] Example 4 was repeated, except that the amounts of catalyst MBO added twice were 0.042 wt% and 0.084 wt% respectively. The results are shown in Table 3.
[0150] Embodiment 17
[0151] Example 4 was repeated, except that the amounts of catalyst MBO added twice were 0.084 wt% and 0.084 wt% respectively. The results are shown in Table 3.
[0152] Embodiment 18
[0153] Example 4 was repeated, except that the amounts of catalyst MBO added twice were 0.084 wt% and 0.126 wt% respectively. The results are shown in Table 3.
[0154] Embodiment 19
[0155] Example 4 was repeated, except that the addition amount of the catalyst MBO was 0.042 wt % and the other catalyst was ZnAc2 and its addition amount was 0.062 wt %. The results are shown in Table 3.
[0156] Embodiment 20
[0157] Example 4 was repeated, except that the catalyst was ZnO, and the amount added twice was 0.062 wt %. The results are shown in Table 3.
[0158] Embodiment 21
[0159] Example 4 was repeated, except that the catalysts TBT and MBO were added in amounts of 0.045 wt % and 0.015 wt %, respectively. The results are shown in Table 3.
[0160] Embodiment 22
[0161] Example 4 was repeated, except that the catalyst was TBT, and the amounts added twice were 0.045 wt% and 0.15 wt% respectively. The results are shown in Table 3.
[0162] Comparative Example 6
[0163] Example 4 was repeated, except that the amounts of catalyst MBO added twice were 0.01 wt% and 0 wt% respectively. The results are shown in Table 3.
[0164] Comparative Example 7
[0165] Example 4 was repeated, except that the amounts of catalyst MBO added twice were 0.15 wt% and 0.15 wt% respectively. The results are shown in Table 3.
[0166] Comparative Example 8
[0167] Example 4 was repeated, except that the catalysts were TBT and Sb2O3, and the amounts added twice were 0.045wt% and 0.05wt% respectively. The results are shown in Table 3.
[0168] Embodiment 23
[0169] Example 4 was repeated, except that the amount of BDO added was 0.92 mol, and another copolymer component, HO-C7-OH, was added in an amount of 0.23 mol. The results are shown in Table 4.
[0170] Embodiment 24
[0171] Example 4 was repeated, except that the amount of BDO added was 1.035 mol, and another copolymer component was HO-C7-OH, which was added in an amount of 0.115 mol. The results are shown in Table 4.
[0172] Embodiment 25
[0173] Example 4 was repeated, except that the amount of BDO added was 1.035 mol, and another copolymer component was HO-C10-OH, which was added in an amount of 0.115 mol. The results are shown in Table 4.
[0174] Embodiment 26
[0175] Example 4 was repeated, except that the amount of TPA added was 0.512 mol, and another copolymer component was IPA, which was added in an amount of 0.128 mol. The results are shown in Table 4.
[0176] Embodiment 27
[0177] Example 4 was repeated, except that the amount of TPA added was 0.576 mol, and another copolymer component, IPA, was added in an amount of 0.064 mol. The results are shown in Table 4.
[0178] Embodiment 28
[0179] Example 4 was repeated, except that the amount of TPA added was 0.576 mol, and another copolymer component, HOO-C10-OOH, was added in an amount of 0.064 mol. The results are shown in Table 4.
[0180] Comparative Example 9
[0181] Example 4 was repeated, except that the diol was EG, and its addition amount was 0.768 mol, and the catalyst was TBT, and its two addition amounts were 0.045 wt% and 0.075 wt% respectively. The results are shown in Table 4.
[0182] Comparative Example 10
[0183] Example 1 was repeated, except that the amount of BDO added was 0.58 mol, the polyol was PER, the amount of which was 0.575 mol, and the terminal modifier SHES was 5.0 mol%. The results are shown in Table 4.
[0184] Comparative Example 11
[0185] Example 1 was repeated, except that the amount of TPA added was 0.576 mol, the sulfonate copolymer component 5-SSIPA was added in an amount of 0.064 mol, and no terminal modifier was added. The results are shown in Table 4.
[0186] Table 1 Examples and Comparative Examples
[0187]
[0188] Table 2 Examples and Comparative Examples
[0189]
[0190] Table 3 Examples and Comparative Examples
[0191]
[0192] Table 4 Examples and Comparative Examples
[0193]
[0194] In Table 1, Examples 1-8 and Comparative Examples 1-3 illustrate that for polyester resins, the laser transmittance of terminal-modified polyester resins with an end base unit content of 0.3 mol%-3 mol% becomes larger, that is, its laser transmittance is significantly improved, and when the content of monomer units derived from SHES is not less than 0.3 mol%, the laser transmittance of the polyester resin can be sufficiently improved; and when the content of monomer units derived from SHES is not more than 3 mol%, while the laser transmittance of the polyester resin increases, its molecular weight Mn is also increased, thereby improving durability and mechanical properties.
[0195] In Table 2, Examples 9-13 and Comparative Examples 4-5 illustrate that for polyester resins, the laser transmittance of the polyester resins blocked by the terminal modifiers shown in Formula 1 and Formula 2 becomes larger, that is, its laser transmittance is significantly improved. However, the laser transmittance of the polyester resins blocked by other terminal modifiers shown in Formula 1 and Formula 2 becomes worse.
[0196] In Table 3, Examples 14-22 and Comparative Examples 6-8 illustrate that for polyester resin, the metal element content is preferably 80ppm-1500ppm, and the prepared polyester resin has a high laser transmittance, which significantly improves the laser transmittance while maintaining a relatively high molecular weight Mn.
[0197] In Table 4, Examples 23-28 and Comparative Examples 9-11 illustrate that for polyester resins, polyester resins prepared from aliphatic diols having 4 to 10 carbon atoms are preferred. The polyester resin prepared in Comparative Example 9 uses an aliphatic diol having 2 carbon atoms, and the laser transmittance is reduced. The polyester resin prepared in Comparative Example 10, in which polyhydroxyl groups and a large amount of terminal blocking agents are introduced, is amorphous and the molecular weight cannot be increased. The laser transmittance of the polyester resin prepared in Comparative Example 11, in which sulfonate dibasic acid is copolymerized, is relatively low, that is, its laser transmittance cannot be improved.
Claims
1. A polyester resin composed of a dicarboxylic acid monomer unit, a diol monomer unit and a terminal group unit, characterized in that: in, The dicarboxylic acid monomer units are mainly derived from aromatic dicarboxylic acids and / or their ester-forming derivatives, the diol monomer units are mainly derived from aliphatic diols having 4 to 10 carbon atoms, the content of the terminal unit is 0.3 mol% or more and 3 mol% or less relative to the total amount of monomer units derived from the dicarboxylic acid component in the polyester resin, and the terminal unit is characterized by a structure represented by Formula 1 or Formula 2; the polyester resin contains at least one of a transition metal or a post-transition metal, and the content thereof relative to the weight of the polyester resin is 80 ppm-1500 ppm; -O-R1-XM Formula 1, In Formula 1, R1 is an alkyl group having 2 to 20 carbon atoms, X is a sulfonic acid group, a carboxyl group, a phosphoric acid group, or a phosphonic acid group, and M is an alkali metal ion or an alkaline earth metal ion; In Formula 2, R2 is an alkyl group having 1 to 20 carbon atoms, a phenyl group or an alkylbenzene, X is a sulfonic acid group, a carboxyl group, a phosphoric acid group or a phosphonic acid group, and M is an alkali metal ion or an alkaline earth metal ion.
2. The polyester resin according to claim 1, characterized in that The content of the monomer units derived from terephthalic acid and / or its ester-forming derivatives is 80-100 mol % relative to the total amount of the monomer units derived from the dicarboxylic acid.
3. The polyester resin according to claim 1, characterized in that The content of the monomer unit derived from 1,4-butanediol is 80 to 100 mol % relative to the total amount of the monomer unit derived from the diol.
4. The polyester resin according to claim 1, characterized in that The terminal unit metal salt is at least one of lithium salt, potassium salt, sodium salt or calcium salt.
5. The polyester resin according to claim 1, characterized in that The terminal group is at least one of an aromatic sulfonate having a carboxylic acid group, an aliphatic sulfonate having a hydroxyl group, or an aliphatic carboxylate.
6. The polyester resin according to claim 1, characterized in that The terminal unit metal salt is at least one of sodium hydroxyethyl sulfonate, sodium hydroxytetradecane sulfonate, sodium 3-carboxybenzene sulfonate and sodium 5-hydroxyvalerate.
7. The polyester resin according to claim 1, characterized in that With respect to the polyester resin, the transition metal and / or post-transition metal element is at least one of tin and zinc.
8. The polyester resin according to claim 1, characterized in that The content of the transition metal and / or post-transition metal element is 200 ppm or more and 1200 ppm or less relative to the polyester resin.
9. The polyester resin according to claim 1, characterized in that The polyester resin is cooled from a molten state to 30°C at a rate of 20°C / min using a differential scanning calorimeter in a nitrogen atmosphere. The top temperature of the exothermic peak caused by crystallization during the cooling process is the crystallization temperature Tmc of the polyester resin. Then the temperature is increased from 30°C at a rate of 20°C / min. The top temperature of the endothermic peak caused by melting during the heating process is the melting point Tm. The temperature difference between the melting point Tm and the crystallization temperature Tmc is less than 25°C.
10. The polyester resin according to claim 1, characterized in that The polyester resin was heat-pressed into a 50 um film at a temperature 25° C. higher than its melting point, and its light transmittance at a wavelength of 940 nm was tested to be above 40%.
11. The polyester resin according to claim 1, characterized in that The number average molecular weight Mn of the polyester resin measured by gel permeation chromatography is greater than 5,000 and less than 20,000.
12. A method for preparing the polyester resin according to any one of claims 1 to 11, characterized in that: The method comprises the following steps: subjecting the diol component, the dicarboxylic acid component and / or its derivative capable of forming an ester and the compound having the structure shown in Formula 1 or 2 to an esterification reaction or an ester exchange reaction in the temperature range of 150 to 250° C., under normal pressure and / or reduced pressure, in the presence of a catalyst, and then subjecting the diol component, the dicarboxylic acid component and / or its derivative capable of forming an ester and the compound having the structure shown in Formula 1 or 2 to a condensation reaction at a temperature of 240 to 270° C. and a pressure of less than 500 Pa; -O-R1-XM Formula 1, In Formula 1, R1 is an alkyl group having 2 to 20 carbon atoms, X is a sulfonic acid group, a carboxyl group, a phosphoric acid group, or a phosphonic acid group, and M is an alkali metal ion or an alkaline earth metal ion; In Formula 2, R2 is an alkyl group having 1 to 20 carbon atoms, a phenyl group or an alkylbenzene, X is a sulfonic acid group, a carboxyl group, a phosphoric acid group or a phosphonic acid group, and M is an alkali metal ion or an alkaline earth metal ion.
13. The method for preparing a polyester resin according to claim 12, characterized in that: During the esterification reaction, transesterification reaction, and condensation reaction, a tin compound and / or a zinc compound is added.
14. A polyester resin composition, characterized in that The polyester resin according to any one of claims 1 to 11 contains a filler in an amount of 0.1 to 150 parts by weight relative to 100 parts by weight of the polyester resin.
15. A molded article, characterized in that: The polyester resin is prepared from the polyester resin according to any one of claims 1 to 11, or the polyester resin composition according to claim 14.
16. The molded article according to claim 15, characterized in that Can be used for laser welding of translucent materials.
Citation Information
Patent Citations
Cationic dye-able polyester composition and preparation method thereof
CN111718479A
Cited By
A method of producing a polyester pellet
TWI915227B